Strengthening Sharia Banking Knowledge Through Educational Initiatives: A Descriptive Qualitative Study - Fitri Indriani, RA Rodia; Marsinah, Marsinah; Marisya, Fitria (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2025)
This study aims to analyze the role of Sharia education in improving Sharia banking literacy among students and students through a descriptive qualitative approach. Data was collected through in-depth interviews, observation of learning activities, and analysis of learning documents, such as modules and activity reports. The study results show that Sharia education strategically strengthens students' understanding of the main concepts of Islamic banking, such as mudharabah, murabahah, and ijarah. Practice-based teaching methods, digital media integration, and banking simulation programs have effectively increased Islamic banking literacy. However, the main challenges are limited learning resources and access to Islamic financial institutions. This study provides academic contributions in mapping effective strategies in Sharia education and recommends collaboration between educational institutions and Sharia finance practitioners to overcome these obstacles